Improving Students' Understanding of Static Fluids Using Virtual Laboratory During the Covid-19 Pandemic - Nanda Rizky Aulia; Edi Supriana; Eny Latifah; Agus Suprapto (Jurnal Pendidikan Sains, 2021)
Abstract: The purpose of this study is to find out the influence of virtual laboratories on static fluid material to improve the understanding of students of class XI during the Covid 19 pandemic. The research design used is a mixed-method with embedded experimental design and samples used in the study of 29 learners. Based on the acquisition of this study, it can be concluded that the use of virtual laboratories equipped with LKS in the field for learning proved to be quite effective because from the acquisition of analytical results explained there is a positive influence on the use of virtual laboratory learning media with a scientific approach to static fluid material to learning outcomes. With this research, it is expected that the use of virtual laboratory learning media can be applied by teachers to physical learning so that learners can easily understand concepts and there are no misconceptions about concepts that exist in physical learning. Abstrak: Penelitian ini bermaksud dapat mengetahui pengaruh virtual laboratory terhadap materi fluida statis dalam meluaskan pemahaman siswa kelas XI di masa pandemi Covid 19. Desain penelitian ini memanfaatkan metode campuran dengan desain embedded experimental dan 29 peserta didik dipergunakan sebagai sampel pada penelitian ini. Berdasarkan perolehan penelitian ini, dapat disimpulkan penggunaan virual laboratory yang dilegkapi dengan LKS didalmnya untuk pembelajaran terbukti cukup efektif karena dari perolehan hasil analisis menjelaskan terdapat pengaruh yang positif penggunaan media pembelajaran virtual laboratory dengan pendekatan saintifik materi fluida statis terhadap hasil belajar. Dengan adanya penelitian ini, diharapkan penggunaan media pembelajaran virtual laboratory dapat diterapkan oleh guru pada pembelajaran fisika sehingga peserta didik bisa lebih mudah mencerna konsep dan tidak mengakibatkan miskonsepsi mengenai konsep-konsep yang ada pada fisika terutama yang berkaitan dengan penerapan fisis pada kehidupan sehari-hari